2023
DOI: 10.1101/2023.06.12.544595
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Typical and disrupted small-world architecture and regional communication in full-term and preterm infants

Abstract: One fundamental property of conscious experiences is that they are both differentiated and integrated. Adult functional brain networks exhibit an elegant "small-world" architecture. This optimal architecture enables efficient and cost-effective localized information processing and information integration between long-distance regions across the brain. It remains unclear whether the functional small-world architecture is developed in neonates at birth and how this development may be altered by premature birth. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 79 publications
(92 reference statements)
0
2
0
Order By: Relevance
“…By mitigating the impact of network density on small-worldness computation, a more direct comparison of topological network structures between groups is enabled, minimizing the influence of density variations (Muldoon et al, 2016). A study by Hu et al (2023), which employed the small-worldness computation suggested by Muldoon et al (2016,) has found that the functional brain network in preterm born individuals showed considerable underdevelopment of small-world architecture compared to term-equivalent age or full-term born neonates. A study investigating the functional networks of young adults, deviations of small-world architectures have been observed in attention deficit hyperactivity (ADHD) and in schizophrenia (Liao et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…By mitigating the impact of network density on small-worldness computation, a more direct comparison of topological network structures between groups is enabled, minimizing the influence of density variations (Muldoon et al, 2016). A study by Hu et al (2023), which employed the small-worldness computation suggested by Muldoon et al (2016,) has found that the functional brain network in preterm born individuals showed considerable underdevelopment of small-world architecture compared to term-equivalent age or full-term born neonates. A study investigating the functional networks of young adults, deviations of small-world architectures have been observed in attention deficit hyperactivity (ADHD) and in schizophrenia (Liao et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to recognize that at least some (and perhaps all) of these markers are experience-dependent and their emergence can be delayed/altered by a variety of factors. For example, premature birth has been associated with disruption to the DMN and frontoparietal networks [ 40 , 69 ] and with an absence of the neural response to surprising sensory omissions that is usually seen at 6 months [ 70 ]. The fact that some of the markers of consciousness can be delayed/altered by adverse environmental conditions does not imply that consciousness itself is delayed (recall that we are treating these markers as one-way rather than two-way markers), but we should certainly take seriously the possibility that consciousness emerges at different times in different individuals.…”
Section: The Case For Early Emergencementioning
confidence: 99%